Combating compassion fatigue. Issue 2 (February 2019) - Perregrini, Michelle
Abstract : Abstract: Nurses are especially susceptible to compassion fatigue. This article offers strategies to help nurses recognize the signs of compassion fatigue, take steps to combat it, and support their coworkers. Abstract : Explore practical strategies that can help nurses recognize compassion fatigue, take steps to combat it, and support coworkers who may also be struggling with it.